Marijampolė County Place-Names Recorded during the Interwar Period: Initial Survey Results and Prospects - Sviderskienė, Dalia (Respectus Philologicus, 2012)
The aim of this article is to present research that has been consistently implemented for several years about the place-names recorded in the “Land Names” questionnaires in Marijampolė County during the interwar period, to discuss their initial findings and to provide for future work. The study is based on the material that was selected as being among the most valuable from a scientific point of view. The unique place-names of Marijampolė County were recorded in thirteen districts during the interwar period from the living language. This authentic material, untouched by external factors such as land melioration, collectivization, Russification, deportation, etc., has been little explored. According to the types of named objects, the database was divided into hydronyms, names of dwelling-places, and toponyms, and evaluated from the point of view of word formation and word origin. The research includes identifying the formation of separate classes and certain trends of origin, studying some classes of toponyms, and investigating the placenames of two districts (Marijampolė and Balbieriškis). The results are interesting, valuable, and relevant. They complement the existing multidimensional habitat list of research and make this almost unpublished lexical resource available to public and scientific society; they also highlight the uniqueness of the toponyms of this habitat and encourage studies of other regions. The research results of interwar material about hydronyms and other place-names derived from personal names in classes (subclasses) are of particular interest and value. The article demonstrates that the extant questionnaires and their authentic material are not only an important separate unit of the interwar legacy, but also a valuable source with recorded facts which have not been preserved in the current collections or significantly changed. The future aim is to collect a complete database of Marijampolė County’s place-names recorded during the interwar period. This will require studying the formation and origin of unstudied place-name units of separate classes (subclasses) and joining the available data with the newly collected. The results will be concretized, supplemented, revised and/or corrected. It is believed that the place-names recorded in this area during the interwar period could provide information about the traces of the onymic substratum of the extinct Baltic tribe of Jatvians.